Foreign Capital Inflows to China, India and the Caribbean Trends, Assessments and Determinants - Banik, A. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
This book takes a unique approach to analysing foreign capital flows. Using the neighbourhood model, it analyzes foreign capital inflows from the perspective of both the source and destination countries. Focusing on China, India and the Caribbean, it explores the direct and spillover effects of foreign capital on the destination countries' economy.